O kuriatku Píp - Sutejev, Vladimir Grigorievič; Ďuríčková, Mária, 1919-2004; Zmatlíková, Helena, 1923-2005 (Bratislava : Mladé letá, 1984)
Kuriatko spoznáva svet.
Keywords: ruská literatúra; príbehy o zvieratkách; predškolský vek